The plenum of the Supreme Court - V.V., Doroshkov (Opción, 2019)
The subject of this study is evaluation of the correlation of the structure, the list of powers of the Plenum with the powers of the bodies of the judicial community, the leadership of the court, executive authorities, etc. The methodology is based on general scientific, interdisciplinary and specially-legal methods of cognition. As a conclusion, for finding the optimal model to build a judicial system, it seems important to find reasonable limits for the division of powers between the bodies of the judicial community and the Supreme Court Plenum which is part of the structure of the highest judicial instance.